(untitled) (Andamios, Revista de Investigación Social, 2013)
The ethnic-cultural discourse of the Mapuche people have been able to adapt to the communication devices that the current global platform offers, virtual circuits going through the Internet Network through hypertext production. These are characterized by a collective subject utterance in an attitude of resistance, fighting performativity with which the mechanisms of domination from the hegemony of mass media, judicial and state have been installed through the making of a conflict that caters only to a part of contention: the “Mapuche conflict “now moved to the virtual space.